IPO Pricing Regulation and Audit Fees: From the Perspective of Institutional Changes in China - Gang Zhao; Ying Deng; Yujia Jiang; Graham Bowrey (Australasian Accounting, Business and Finance Journal, 2023)
From the perspective of institutional change in IPO regulation, this paper discusses the relationship between IPO pricing regulation and audit fees in China. This paper finds that the audit fees of IPO companies are higher in the stage of pricing regulation in comparison to the stage of pricing marketization. We also find auditors charge higher audit fees for private companies than state-owned companies during the IPO pricing regulation period. Furthermore, in regions with tightened legislation, IPO audit fees are higher in the IPO pricing regulation period.
Keywords: Institutional changes; IPO pricing regulation; Audit Fees; Audit risk